Applying the ‘least dangerous assumption’ in regard to behaviour policies and children with special needs - Emerson, Anne (Taylor & Francis, 2016)
Children with special needs and disabilities (SEND) in mainstream schools have a wide range of complex conditions rendering it impossible for teachers to fully understand all the complexities of their needs. Difficulties with understanding and self-control lead to much of the behaviour that is considered unacceptable within schools and that can ultimately lead to the large numbers of children with SEND who are excluded. Schools often wish to provide a behaviour policy where everyone is treated equally despite people’s needs and abilities being different. Government guidance in relation to behaviour policies is that they should comprise a mixture of sanctions and rewards, but this behaviourist view leads to a lack of equity of response to behaviour, again feeding into disproportionate numbers of children with SEND being excluded. The move from sanctions and rewards to the operation of a relationships policy where students’ actions yield consequences, within a humanist ethos of understanding, would far more effectively support all children to learn to moderate and control their behaviour and would allow staff to apply the ‘least dangerous assumption’ when dealing with challenging students.